Synthesis Characterization and Biological Activities of Coordination Compounds of 4-Hydroxy-3-nitro-2 H -chromen-2-one and Its Aminoethanoic Acid and Pyrrolidine-2-carboxylic Acid Mixed Ligand Complexes2016 - Aiyelabola, Temitayo; Akinkunmi, Ezekiel Olugbenga; Obuotor, Efere Martins; Idowu, Olawuni (Hindawi Publishing, 2020)
Bioinorganic Chemistry and Applications, Vol. 2017, 9 pages